Ferroelectricity in van der Waals multilayers via interfacial polarization engineering - Xiaokai Chen; Xiaoyu Xuan; Wanlin Guo; Zhuhua Zhang (npj 2D Materials and Applications)
Abstract We report a general mechanism for building ferroelectricity in prevailing van der Waals (vdW) multilayers via interfacial engineering. Using sandwiched graphene/boron nitride (BN)/graphene multilayers as an exemplary system, we show that considerable electric polarization can arise at graphene/BN interfaces where charge redistribution enhances intralayer electric dipoles. Moreover, the electric polarization between BN layers is concertedly enhanced due to interlayer compression driven by an extraordinary cross-layer electrostatic attraction. Then, the interfacial polarization and enhanced interlayer polarization can serve as two elements for building robust ferroelectrics from vdW multilayers with cumulative, thickness-controllable polarization. We demonstrate this mechanism in generating an electric polarization of 1.0 pC/m in a nominally nonpolar BN monolayer sandwiched between graphene layers, and up to 4.2 pC/m in a sandwiched BN quadrilayer. These results underscore the previously unnoticed role of unavoidable hetero-interfaces in contributing to the observed ferroelectricity in diverse vdW devices.